Antioxidant Activity And Tirosinase Enzyme Inhibition Of Pandan Leaf Extract (Pandanus Amaryllifolius) - Amelia Trisnawati Lubis; Edy Fachrial; Nerly Juli Pranita Simanjuntak Leki (International Journal of Health Engineering and Technology, 2026)
Continuous exposure to ultraviolet radiation triggers the formation of Reactive Oxygen Species (ROS), leading to oxidative stress and damage to cellular biological components. This condition is closely associated with increased activity of the tyrosinase enzyme, a key enzyme in the melanin biosynthesis process that can cause hyperpigmentation. This study aims to evaluate the antioxidant activity and tyrosinase enzyme inhibition potential of the ethanolic extract of pandan leaves (Pandanus amaryllifolius) in vitro. The research method began with the extraction of pandan leaf powder using 70% ethanol as a solvent. Subsequently, qualitative  phytochemical screening was conducted to identify secondary metabolites. The antioxidant activity was evaluated using the DPPH method across various concentrations, with Vitamin C as the standard comparison. The tyrosinase enzyme inhibition assay was performed spectrophotometrically using L-DOPA as a substrate at a wavelength of 492 nm. Phytochemical screening revealed that the extract contains secondary metabolites, including flavonoids, alkaloids, saponins, and tannins. The antioxidant test using the DPPH method showed that at a concentration of 500 ppm, the extract achieved an inhibition percentage of 97.73%, which is comparable to the effectiveness of Vitamin C (99.36%). In the tyrosinase enzyme assay using L-DOPA as a substrate, the blank absorbance was 0.794, while the sample absorbance was 0.907. Although the sample absorbance was higher due to the extract's intrinsic color pigments, the calculation indicated a very strong enzyme inhibition effectiveness of 90.7%. In conclusion, the ethanolic extract of pandan leaves (Pandanus amaryllifolius) holds significant scientific potential as a natural therapeutic agent to counteract oxidative stress and inhibit melanogenesis in skin pigmentation disorders.